Marketing strategy development for MSME based on the Korean Wave - Yusuf, Mochammad; Pratiwik, Erida; Berlianti, Erni Nelia; Kistanti, Nurjannah Rahayu (MBR (Management and Business Review), 2023)
Korean culture is currently growing rapidly and expanding globally in the last two decades, known as the Korean Wave. One of the impacts of this phenomenon in Indonesia includes shifting social, cultural, and economic trends. This study aimed to examine the influence of the Korean Wave on consumer purchasing decisions and its use as a marketing strategy development for MSME in Semarang City. The method adopted is Moderating Regression Analysis and Analytical Hierarchy Process. The results showed that brand image and the Korean wave have a significant relationship with purchasing decisions. The Korean Wave was meant to moderate the relationship between brand image and purchasing decisions. In an effort to develop a Korean wave-based marketing strategy, food and fashion actors are advised to insert a call to action sentence, select online marketing media that are often used by the community, optimize AdSense, and use the lowest possible production costs.